Geographic Information System Using Postgre SQL-QGIS for Slum Squatter Distribnution Mapping in North Jakarta - Rizkan Gaffara, Ghefra; Maratis, Jerry; Sitoayu, Laras; Adi Pamungkas, Rian; Ummanah, Ummanah (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research aim to build a geographic information system that displays a mapping of slum building distribution in North Jakarta. One of spatial software was developed using a method is the Rational Unified Process (RUP) method. This research aim to build a geographic information system that displays a mapping of building distribution in North Jakarta. This system was built using Postgre SQL and QGIS to build map. The research finding in the research is that there is a tendency for built-up areas to grow in slum areas due to the absence of rental fees, land and building costs, but the feasibility conditions of these areas are very unsuitable. This research is limited to implementing the use of Postgre SQL and QGIS software. Because the rendering process for the visual display is very difficult. I hope that in the future this research will be developed interesting 3D visualization accompanied by charts. The implication of this research is to make it easier to see the distribution of dense and slum areas and become a step for the government in making policies. The originality of this research is that there is still no one who combines the two software in mapping analysis.